2017
DOI: 10.1292/jvms.15-0674
|View full text |Cite
|
Sign up to set email alerts
|

Association between liver failure and hepatic UDP-glucuronosyltransferase activity in dairy cows with follicular cysts

Abstract: Uridine 5’-diphospho-glucuronosyltransferase (UGT) liver activity was measured using estradiol-17β as a substrate in dairy cows with follicular cysts. The activity was significantly lower than that in dairy cows with normal estrous cycles (P<0.01). Liver disorders, such as fatty liver and hepatitis, were observed in half cows with follicular cysts, and liver UGT activity was lower than that in cows with normal estrus cycles. In addition, the liver UGT activity was significantly lower in dairy cows with follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…UGT2A3, UGT2B35, and UGT1A1 belong to UDP glucuronosyltransferase family (UGTs) (Tanemura et al, 2017 ). UGTs are the main phase II drug metabolic enzymes that can catalyze glucuronic acid from UDP-glucuronic acid (UDPGA) to transfer to exogenous substances, and improve water solubility of the receptor, then expel from the body.…”
Section: Resultsmentioning
confidence: 99%
“…UGT2A3, UGT2B35, and UGT1A1 belong to UDP glucuronosyltransferase family (UGTs) (Tanemura et al, 2017 ). UGTs are the main phase II drug metabolic enzymes that can catalyze glucuronic acid from UDP-glucuronic acid (UDPGA) to transfer to exogenous substances, and improve water solubility of the receptor, then expel from the body.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of circulating ALT may reflect the underlying liver pathology. A recent study that revealed half of FC cows with liver disorders, such as fatty liver and hepatitis ( 47 ). This finding suggests that liver disorders are well-connected to development of FC in dairy cows and that steroid hormone metabolism is delayed, resulting in the formation of FC ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that revealed half of FC cows with liver disorders, such as fatty liver and hepatitis ( 47 ). This finding suggests that liver disorders are well-connected to development of FC in dairy cows and that steroid hormone metabolism is delayed, resulting in the formation of FC ( 47 ). On the contrary, we observed that FC cows had lower plasma ALT levels, and we postulate that an enhanced hepatic lipid mobilization accounts for this phenomenon ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Крім того, на порядок знизився показник прояву ендометриту, що, на нашу думку, пов'язано з нормалізацією гормонального (естрадіолпрогестеронового) профілю організму корів. Це також підтверджують дослідження іноземних авторів (Ortega et al, 2016;Tanemura et al, 2017;Kengaku et al, 2021). Висновки 1.…”
Section: обговоренняunclassified